INDUKSI TUNAS PISANG KEPOK (Musa paradisiaca L.) MENGGUNAKAN KOMBINASI KINETIN DAN IAA SECARA IN VITRO - BOER, DIRVAMENA; PRAWANSA, AGUNG; RAKIAN, TRESJIA CORINA; ARSYAD, MIRZA ARSIATY; ARIF, NORMA; MADIKI, ABDUL; ARSANA, I MADE WISANA (Jurnal Agroteknos, 2024)
This study aims to investigate the effect of combining Kinetin and IAA on the growth of kepok banana shoots in vitro. The research was conducted at the In Vitro Laboratory, Agrotechnology Unit, Faculty of Agriculture, Halu Oleo University, from January to April 2023. The study utilized a Completely Randomized Design (CRD) with six treatments: P1 = (Kinetin 1 mg L⁻¹ + IAA 2 mg L⁻¹), P2 = (Kinetin 3 mg L⁻¹ + IAA 4 mg L⁻¹), P3 = (Kinetin 5 mg L⁻¹ + IAA 6 mg L⁻¹), P4 = (Kinetin 2 mg L⁻¹ + IAA 1 mg L⁻¹), P5 = (Kinetin 4 mg L⁻¹ + IAA 3 mg L⁻¹), and P6 = (Kinetin 6 mg L⁻¹ + IAA 5 mg L⁻¹). Each treatment had five replicates, resulting in 30 experimental units, with four Kepok banana shoot explants per culture bottle. The observed variables included shoot emergence time, number of shoots, shoot length, and shoot growth percentage. Results indicated that the combination of Kinetin and IAA concentrations significantly affected the number of shoots and shoot emergence time and shoot length, but did not significantly affect the shoot growth percentage. The best treatment was P2 = (Kinetin 3 mg L⁻¹ + IAA 4 mg L⁻¹) for in vitro growth of Kepok banana shoots.